Efektivitas Metode Instruksi Segmentasi Fonemik terhadap Kesadaran Fonemik pada Anak dengan Keterlambatan Bicara - Anindya Yuniar (Jurnal Syntax Admiration, 2025)
This study is an experimental study that aims to determine the effectiveness of the Phonemic Segmentation instruction method on Phonemic Awareness in children with Speech Delay in children aged 5-6 years. This research design uses One-group Pretest-posttet group. The sample of this study involved 16 subjects who live in Jakarta and pre-school learning group. Data collection techniques obtained from the results of Pretest and posttest scores. The analysis technique used includes Shapiro Wilk normality test and Wilcoxon statistical test which is processed using SPSS version 23. The results of the analysis show that the significance value is 0.001 <0.005, then Ho is rejected and Ha is accepted or it can be concluded that there is a difference in Phonemic Awareness before intervention and after intervention in children with Speech Delay. The results showed that the average value increased by 41% which means that Phonemic Awareness in children with Speech Delay increased after the Phonemic Segmentation Instruction method was given.